2019
DOI: 10.1158/0008-5472.can-19-0454
|View full text |Cite
|
Sign up to set email alerts
|

Meflin-Positive Cancer-Associated Fibroblasts Inhibit Pancreatic Carcinogenesis

Abstract: Cancer-associated fibroblasts (CAF) constitute a major component of the tumor microenvironment. Recent observations in genetically engineered mouse models and clinical studies have suggested that there may exist at least two functionally different populations of CAFs, that is, cancer-promoting CAFs (pCAF) and cancer-restraining CAFs (rCAF). Although various pCAF markers have been identified, the identity of rCAFs remains unknown because of the lack of rCAFspecific marker(s). In this study, we found that Meflin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
222
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 230 publications
(255 citation statements)
references
References 51 publications
13
222
0
Order By: Relevance
“…Furthermore, these CAF were found to also be positive for Gli1, a transcription factor critical for Shh signaling, consistent with previous findings that describe the cancer‐promoting effect of Shh deletion in cancer cells . We have also shown that Meflin is specifically expressed in PSC within the normal pancreas . Hence, it is feasible to hypothesize that Meflin + PSC proliferate to become rCAF during tumorigenesis of PDAC (Figure 2A).…”
Section: Meflin: a Candidate Marker Of Cancer‐restraining Cancer‐assosupporting
confidence: 90%
See 4 more Smart Citations
“…Furthermore, these CAF were found to also be positive for Gli1, a transcription factor critical for Shh signaling, consistent with previous findings that describe the cancer‐promoting effect of Shh deletion in cancer cells . We have also shown that Meflin is specifically expressed in PSC within the normal pancreas . Hence, it is feasible to hypothesize that Meflin + PSC proliferate to become rCAF during tumorigenesis of PDAC (Figure 2A).…”
Section: Meflin: a Candidate Marker Of Cancer‐restraining Cancer‐assosupporting
confidence: 90%
“…As mentioned above, Meflin + CAF weakly express α‐SMA, suggesting that in the previous study, in which all proliferating α‐SMA + CAF were genetically depleted, a portion of Meflin + CAF were also eradicated (Figure 2A). Together, the data, including data not described here, suggest that Meflin + α‐SMA low/− CAF represent rCAF in PDAC. Furthermore, these CAF were found to also be positive for Gli1, a transcription factor critical for Shh signaling, consistent with previous findings that describe the cancer‐promoting effect of Shh deletion in cancer cells .…”
Section: Meflin: a Candidate Marker Of Cancer‐restraining Cancer‐assosupporting
confidence: 60%
See 3 more Smart Citations